H∞ observer design for a class of nonlinear singular stochastic systems. Issue 1 (July 2017) - Barbata, Asma; Zasadzinski, Michel; Ali, Harouna Souley
Abstract: This paper is about the H ∞ observer design for a class of nonlinear singular stochastic systems. The system is first transformed such that the observation error can be written in a regular form and the augmented system is admissible. The use of Sylvester-like equations on the error dynamics permits to parameterize all the filter matrices via a single gain matrix. Then an affine change of coordinate is done on the control inputs to transform the problem into a singular robust stochastic nonlinear problem which is solved using a Lyapunov approach. Finally the mean square exponential stability (MSES) of the error's system and the H ∞ disturbance attenuation are ensured by the observer designed via the resolution of a LMI which permits to get the gain matrix used to construct the filter matrices.